PENGARUH KANDUNGAN PARTIKEL SERBUK GENTENG SOKKA TERHADAP KEKUATAN TARIK DAN KEKUATAN IMPAK PADA KOMPOSIT BERMATRIKS EPOXY - Nugroho, Fajar (Sekolah Tinggi Teknologi Adisutjipto, 2017)
Abstract— Composites consist of two or more separate materials combined in a macroscopic structure. This is different from alloy which is the structural unit is formed microscopiccally. At this research, the composite reinforcement was made of sokka Kebumen powder tile using epoxy formatrix. The percentage variations of volume fraction are 0%, 10%, 20%, 30%, and 40% with a mesh size of 180-200 mesh. This study aims to determine the tensile strength, impact strength, and SEM. The method used during the manufacturing process of composite was vacum molding. The tensile strength test showed the highest value was at 10% volume fraction with 49,946 MPa. The lowest value was at 40% volume fraction with 27,618 MPa. The impact strength test showed the highest value was at 10% volume fraction with 0,03925 J/mm2. The lowest value was at 40% volume fraction with 0,03375 J/mm2. The higher the percentage volume fraction of sokka tile powder, the lower the tensile strength and the impact strength of the composites have. The SEM test showed that there was still pull out at the side. Keywords: sokka tile powder, epoxy, volume fraction, composite.